DESIGN AND SYNTHESIS OF NOVEL IMIDAZO[1,2-A]PYRIDINE DERIVATIVES AND THEIR ANTI-BACTERIAL ACTIVITY - Budumuru, Pushpalatha; Golagani, Srinivasarao; Kantamreddi, Venkata Siva Satyanaryana (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study aims to synthesize a novel derivatives of Imidazo[1,2-a]pyridines and the compounds were evaluated for their antibacterial activity. Methods: A series of newly synthesized compounds were characterized by 1H-nuclear magnetic resonance (NMR), 13C-NMR, Fourier transform infrared, mass spectral analysis, and screened for their antibacterial activity by disc diffusion method. Molecular docking studies were performed with a bacterial beta subunit of DNA gyrase using Auto Dock 4.2.6, and the docked conformations were analyzed using visual molecular dynamics. Results: The structural activity relationship of the synthesized imidazo[1,2-a]pyridine derivatives was studied against Gram-positive and Gram-negative bacteria. Among the synthesized compounds N-benzyl-4-((2-(6-methyl-2-(p-tolyl)imidazo[1,2-a]pyridin-3-yl) acetamido)methyl) benzamide (9a) are possessing high activity against Bacillus subtilis. The zone of inhibition produced by the compound 9a is wider than that of remaining compounds used in this study. Conclusion: The synthesized compounds exhibited good antibacterial activity in comparison with standard drug streptomycin. This suggests that the compound 9a and its analogs are exerting their activity by probably inhibiting bacterial beta subunit of DNA gyrase.